Cardiovascular risk factors associated with oxidative stress in adolescents with overweight and obesity. (Revista Venezolana de Salud Pública, 2020)
The increase of reactive oxygen species is generated when oxidative conditions occur, as in obesity and lead to chronic diseases such as high blood pressure. Oxidative stress has been reported as a trigger and result of high blood pressure, which affects cardiovascular health. The objective of the present study was to determine oxidative stress and its association with Cardiovascular Risk Factors (CVRF) in overweight and obese adolescents, for this clinical and paraclinical parameters were determined, and cardiovascular risk factors were evaluated, such as hypertension, dyslipidemia, obesity, overweight and markers of oxidative stress. The sampling was non-probabilistic and consisted of 34 adolescents, with ages between 13 and 19 years, which were grouped according to the value of Body Mass Index (BMI) in normal (BMI between 18.5 and 24.9) with 10 patient and overweight/obesity (BMI greater than 25). The data were analyzed with the statistical package SPSS version 19, the averages ± the standard deviation is presented, additionally a multiple linear regression model was applied for each of the dependent variables used to determine the oxidative stress, statistical significance was accepted before values of p≤0.05. In the adolescents studied, no association was found between the cardiovascular family history and the evaluated variables, in addition, greater oxidative stress was observed in overweight/obese patients, statistically significant and association with BMI, urea and total cholesterol. In conclusion, there is an association between oxidative stress and CVRF in adolescents with a BMI greater than 25.
Keywords: Obesity; overweight; cardiovascular risk factors; oxidative stress